The Effectiveness of Curfew Hours in Barangay Payatas Quezon City: Vol.4, No.1 (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study identified the effectiveness of Curfew Hours in Barangay Payatas Quezon City. Itwas focused on the demographic profile, the factors that influence the effectiveness of curfewhours, and the problems encountered by Barangay Payatas Quezon City.The findings of the study revealed that most of the respondents were thirty (30) years old andabove, with a frequency of thirty-two (32) or 45.71%. The majority of the respondents weremale, with a frequency of forty-six (46) or 65.71%. On the factors that influence theeffectiveness of curfew hours, the study showed that crime rate was the highest factor, with aweighted mean of 3.52 and an interpretation of “strongly agree.” On the other hand, the studyshowed that the rank one problem encountered by the Barangay Payatas was the rudebehavior of the community when violating curfew hours or being detained. Lastly, the studyshowed that the measures that should be proposed to address the problem encountered werethe curfew advisory board with a weighted mean of 3.74 and verbal interpretation of “stronglyagree.”As a result of the research, it was suggested that the Barangay Payatas should explore thepotential role of community-based interventions that can improve the relationship betweenauthorities and the community, such as education programs, community awareness, andassembly between families and barangay personnel to support family needs. In addition, theBarangay Payatas should conduct a more comprehensive study on curfew hours in regard tothe economic progress in the community. Finally, examine the workforce and the strategicplan for implementing curfew hours.
Keywords: Criminology